Plasma Dermatology: Skin Therapy Using Cold Atmospheric Plasma - Tan, Fei; Wang, Yang; Zhang, Shiqun; Shui, Runying; Chen, Jianghan (Frontiers in Oncology, 2022)
Cold atmospheric plasma-based plasma medicine has been expanding the diversity of its specialties. As an emerging branch, plasma dermatology takes advantage of the beneficial complexity of plasma constituents (e.g., reactive oxygen and nitrogen species, UV photons, and electromagnetic emission), technical versatility (e.g., direct irradiation and indirect aqueous treatment), and practical feasibility (e.g., hand-held compact device and clinician-friendly operation). The objective of this comprehensive review is to summarize recent advances in the CAP-dominated skin therapy by broadly covering three aspects. We start with plasma optimisation of intact skin, detailing the effect of CAP on skin lipids, cells, histology, and blood circulation. We then conduct a clinically oriented and thorough dissection of CAP treatment of various skin diseases, focusing on the wound healing, inflammatory disorders, infectious conditions, parasitic infestations, cutaneous malignancies, and alopecia. Finally, we conclude with a brief analysis on the safety aspect of CAP treatment and a proposal on how to mitigate the potential risks. This comprehensive review endeavors to serve as a mini textbook for clinical dermatologists and a practical manual for plasma biotechnologists. Our collective goal is to consolidate plasma dermatology’s lead in modern personalized medicine.